The degree of using "My School’s" website and its role in improving the school management effectiveness in West Bank schools from the principals' perspectives - Al-Awawdeh, Intisar Taleb Jaber (Journal of Educational and Psychological Sciences, 2022)
The study aimed at knowing the degree of using "My School’s" website and its role in improving the school management effectiveness in West Bank schools from the principals ' perspectives, and to know the effect of some variables (directorate of education, the gender of the principals, and the age of the principals) on the degree of use of "My School’s " website. The descriptive approach was used in the research, and the questionnaire was used as a tool for the study, its validity and reliability were verified, and its reliability coefficient was according to Cronbach’s alpha test (0.97). The total degree of using my school website in improving the effectiveness of school administration in West Bank schools from the point of view of the principals is a medium degree with an arithmetic mean (3.21). Planning with an arithmetic mean (3.06), then evaluation with an arithmetic average (3.06), then communication with an arithmetic mean (2.73). There are statistically significant differences at the significance level (α≤0.05) in the degree of using my school website and its impact on improving the effectiveness of school administration in schools of The West Bank from the point of view of the principals is attributed to males, and there are no statistically significant differences attributed to the Directorate of Education or to the age of the principal. The researcher recommended the need to develop my school website to serve the school administration according to its fields by providing it with appropriate content of data and files that are used, whether in planning, organizing, or evaluation, and developing the possibility of effective electronic communication between all human resources in the school, education and parents of students.
Keywords: school administration; effective principal; effective school; planning; evaluation